2005
DOI: 10.1111/j.1601-1546.2005.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue management: flap design, incision, tissue elevation, and tissue retraction

Abstract: The ultimate goal in surgical endodontics is not only the eradication of periapical pathosis but also preservation of periodontal conditions using suitable surgical techniques. Acceptable treatment outcomes are no longer possible without consideration of esthetic consequences for all involved dentoalveolar structures. During surgical endodontics the cortical bone is exposed by incising, elevating, and reflecting a full‐thickness tissue flap. Certain basic principles must be considered before deciding on the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Tissue flap designs should allow the maintenance of optimal and sufficient blood supply to all parts of the mobilized and immobilized portions of the soft tissues (1). With prolonged duration of the surgical procedure, especially when a high degree of hemostasis has been achieved, there is a risk of drying out of the tissues.…”
Section: Surgical Site Closurementioning
confidence: 99%
See 1 more Smart Citation
“…Tissue flap designs should allow the maintenance of optimal and sufficient blood supply to all parts of the mobilized and immobilized portions of the soft tissues (1). With prolonged duration of the surgical procedure, especially when a high degree of hemostasis has been achieved, there is a risk of drying out of the tissues.…”
Section: Surgical Site Closurementioning
confidence: 99%
“…In principle, a tissue flap consists of gingival and mucosal tissues as well as periosteum. Various modes of incisions can be selected prior to tissue elevation and reflection (1). The prime objective of periapical surgery is to provide conditions such that healing and repair or regeneration can occur.…”
Section: Introductionmentioning
confidence: 99%
“…Good access and visibility of the surgical field is one of the principle requirements of periapical surgery and the manipulation of the soft tissues must be performed without compromising the requirements for optimal access to the periapical region and perfect visibility of the involved apical structures [3,4].Although the results of comparison were statistically insignificant; OL flap was found to be adequate in 9 patients as compared to 7 patients of the TZ flap group. In a similar study visibility was assessed by the operator's personal experience during holding of flap by assistant, facilitation of visibility during cutting bone and assistance in lip retraction and it was found that OL flap is much better in all the respects [4].…”
Section: Discussionmentioning
confidence: 73%
“…In a similar study visibility was assessed by the operator's personal experience during holding of flap by assistant, facilitation of visibility during cutting bone and assistance in lip retraction and it was found that OL flap is much better in all the respects [4].…”
Section: Discussionmentioning
confidence: 99%
“…Flap designs have been somewhat modified to provide enhanced outcomes (12,(140)(141)(142)(143)(144)(145)(146). However, the ultimate response will be highly dependent on the endodontic surgeon, the choice of flap design based on the anatomy of both the soft and hard tissue, the extent of pathosis when present, attention to detail during the surgical procedure, and management during wound closure (147).…”
Section: Soft Tissue Managementmentioning
confidence: 99%